PRINSIP DIFERENSIASI AL QUR’AN PERSPEKTIF MUHAMMAD SHAḤRŪR
This research is a study of deconstruction carried out by Shahrur about key terms in the Qur'an. Among them are al-Kita>b, al-Qur’a>n, al-Dhikr, Tafs